The controversial role and therapeutic development of the m6A demethylase FTO in renal cell carcinoma - Dalin Zhang; Sarah Wornow; Donna M. Peehl; Erinn B. Rankin; James D. Brooks (Translational Oncology, 2022)
Fat mass and obesity-associated (FTO) protein, the first m6A demethylase identified in 2011, regulates multiple aspects of RNA biology including splicing, localization, stability, and translation. Accumulating data show that FTO is involved in numerous physiological processes and is implicated in multiple cancers including renal cell carcinoma (RCC). However, the exact role of FTO in RCC remains controversial. Some studies demonstrated that decreased FTO expression was associated with aggressive clinical features and shorter overall survival in clear cell RCC (ccRCC) patients, while others found that FTO inhibition selectively reduced the growth and survival of VHL-deficient ccRCC cells in vitro and in vivo. Here, we review the evidence supporting either a promoting or suppressive role of FTO in kidney cancers, the mechanisms of action of FTO, and recent progress in developing FTO inhibitors.